Intensive mothering in hard times: Foucauldian ethical self-formation and cruel optimism. (November 2019) - Cappellini, Benedetta; Harman, Vicki; Marilli, Alessandra; Parsons, Elizabeth
Discourses of intensive mothering now seem to dominate European and American parenting cultures. This is a problem for those mothers who do not currently possess the resources to match up. In a study of Italian and British mothers who are experiencing low or reduced incomes, we observe the ways in which they internalize intensive mothering discourses through a process of ethical self-formation. This mode of self-formation involves detailed self-surveillance and self-discipline and abnegation of their own needs in place of other individual family members, and the family as a whole. We find a series of contradictory emotional effects which generate both pride and self-worth but also stress and anxiety. We advance the theory that mothers operate within an optimistic affective regime to make sense of these contradictory effects and retain a sense of agency and control over their lives and those of their families. However, drawing on Berlant's concept of cruel optimism, we argue that such affective regimes may be very pernicious in their effects, only serving to hold mothers in a relation that is ultimately impassable and often unfulfilling.